Percepção pública da ciência e da tecnologia dos medicamentos: subsídios para o ensino de ciências - Pedrancini, Vanessa Daiana [UNESP] (2015)
Science and tecnology have manifested their importance within contemporary culture through the development of a great number and different types of innovations that permeate different areas in social life. On the other hand and at the same time, a process of demystification of science is in progress. Science is faced with it its own success, deficits, failures, suffering, issues that should be overpassed and unfulfilled promisses. The public understanding of scientific and tehcnological applications with regard to the risks, limits, implications ans benefits is basic within the context of community decisions and individual choices. Current analysis aims at understanding the public perception an the Science and Technology of Drugs to subsidy the teaching of Science though a research instrument that would undertake a quantitative investigation. A questionnaire was applied to a sample of 551 inhabitants of the municipality of Maringá PR Brazil on the following issues: valorization of licit drugs as a usefull application for the solution of problems and improvement in life quality; trust in the S&T of drugs and the perception of risks; degree of information and interest with regard to drugs and the most used sources by people to be informed on the theme. The internet may be underscored among the most cited sources of information by people to solve their doubts on drugs. Althrough the population showed an interest in being informed on the theme, the most interested people were not always those who were most informed. With regard to trust in drugs, the answers strengthened predominant culture among the population, or rather, the valorization of knowledg derived from scientific activities. Further, a positivist and salvationist stance with regard to S&T was provided, albeit not with extreme positions, since certain limitations in scientific and technological development were acknowledged to solve problems or improve life quality through licit...